1990
DOI: 10.1002/tea.3660271004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of concept mapping on students' anxiety and achievement in biology

Abstract: The results of recent studies into the use of the concept mapping heuristic seem to demonstrate that meaningful learning results through its use in science classrooms. While this underscores the need to use more effective instructional strategies in science teaching, the issue of the intervening variable of anxiety in learning and science achievement, and the possible use of a metacognitive strategy in anxiety reduction have not been addressed. This study, therefore, sought to find out if the metacognitive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 20 publications
4
39
1
3
Order By: Relevance
“…These diagrams allow students to map their understanding o f a particular content area. Heinze-Fry and Novak (1990) Concept maps have been used successfully in many different disciplines, and with students from elementary school to graduate school (Heinze-Fry & Novak, 1990;Novak, Gowin, & Johansen, 1983;Starr & Krajcik, 1990;Willerman & Mac Harg, 1991;Beyerbach & Smith, 1990;Okebukola, Alaiyemola & Jegede, 1990;Okebukola, 1990;Okebukola & Jegede, 1989;Pankratius, 1990;Wallace & Mintzes, 1990). They can also be used with students who differ in intellectual ability (Malone & Dekkers, 1984).…”
Section: The Influence Of Concept Mapping On Achievement Self Regulamentioning
confidence: 99%
See 1 more Smart Citation
“…These diagrams allow students to map their understanding o f a particular content area. Heinze-Fry and Novak (1990) Concept maps have been used successfully in many different disciplines, and with students from elementary school to graduate school (Heinze-Fry & Novak, 1990;Novak, Gowin, & Johansen, 1983;Starr & Krajcik, 1990;Willerman & Mac Harg, 1991;Beyerbach & Smith, 1990;Okebukola, Alaiyemola & Jegede, 1990;Okebukola, 1990;Okebukola & Jegede, 1989;Pankratius, 1990;Wallace & Mintzes, 1990). They can also be used with students who differ in intellectual ability (Malone & Dekkers, 1984).…”
Section: The Influence Of Concept Mapping On Achievement Self Regulamentioning
confidence: 99%
“…However, most studies used concept mapping as a metacognitive strategy (Novak, 1987;Kim, German, & Patton, 1998;Okebukola & Jegede, 1989;Okebukola, Alaiyemola & Jegede, 1990). For instance, Novak (1987) indicated that concept mapping is a metacognitive strategy because it assists learners in understanding concepts and relationships among these concepts and in seeing the hierarchical, conceptual, and prepositional nature o f knowledge.…”
Section: Chapter Two Review Of the Literature Theoretical Foundationsmentioning
confidence: 99%
“…Concept maps have been used in the study of physics (Roth and Roychoudhury 1994;Gangosa 1996), chemistry (Stensvold and Wilson 1990;Markow and Lonning 1998), ecology and environmental education (Brody 1993;Heinze-Fry 1997), biology (Heinze-Fry and Novak 1990;Jegede, Alaiyemola and Okebukola 1990;De Groot 1993;Markham 1993;Songer and Mintzes 1993;Farrokh and Krause 1996;Coleman 1998), history (Baldissera 1993), astronomy (Zeilik, Schau, Mattern, Hall, Teague and Bisard 1997), veterinary medicine (Edmondson 1995), engineering (Moreira and Greca 1996), literature (Leahy 1989;Moreira 1996), geology (González Concept Maps as Assessment . .…”
Section: Previous Uses Of Concept Mapsmentioning
confidence: 99%
“…For example, Okebukola and Jegede (1989) reported that the use of concept mapping reduces anxiety of students who were studying subject matter that they perceive to be difficult. Jegede, Alaiyemola, and Okebukola (1990) also reported similar results, but suggested that the reduction of anxiety towards the subject matter was more prominent in males than in females.…”
Section: International Journal Of Research Studies In Educational Tecmentioning
confidence: 58%